'Felt like a fish out of water': second-generation Turkish-German returnees' narratives of educational (dis-)integrations and selective acculturation paths in Turkey. - Kılınç, Nilay (Journal of Ethnic & Migration Studies, 2025)
This paper explores the impact of family return migration on the educational experiences of second-generation Turkish-German youth who relocated to their parental homeland. Drawing on life-story narratives from 32 second-generation returnees in Turkey, the paper examines their structural and sociocultural (dis-)integrations within new educational settings. The paper employs the frameworks of selective acculturation and translocational positionality to analyse how returnees navigated their identities and pursued educational and career pathways that utilised their German language skills and transnational educational backgrounds. The participants faced several challenges that impeded their academic progress, including the non-recognition of their German qualifications, authoritarian teaching style, rote learning methods, and limited proficiency in academic Turkish. Additionally, participants were often stigmatised by peers as Almancı ('German-like'), a term linked to a distinct socio-economic identity shaped by their background as children of labour migrants. Return migration also created opportunities, particularly for those who had faced discrimination in the German education system. Most returnees secured places at Turkish universities through German-language tests and special entrance exams designed for 'foreign' students. The findings suggest that selective acculturation, where second-generation returnees retain aspects of their German upbringing while adapting to Turkey's social and educational environment, facilitates improved academic success and career advancement.